Monday

March 30, 2015

March 30, 2015

Posted by **kiearia** on Wednesday, January 6, 2010 at 9:36pm.

**Answer this Question**

**Related Questions**

math - solve by using subsitution: 4x+y=2 3y+2x=-1

math - solve by using subsitution: 4x+y=2 3y+2x=-1

math - solve by using subsitution: 4x+y=2 3y+2x=-1

math - solve by using subsitution: 4x+y=2 3y+2x=-1

math - solve by using subsitution: 4x+y=2 3y+2x=-1

algebra - explain how you solve 11x=3y=12 using 3x=9 as subsitution

subsitution method - Can some one show me how to use the Substitution method to ...

algebra - solve using the subsitution method 4x+4y=36 4x+4y=12 If the system has...

7th grade math - How would you solve the problem below using the subsitution ...

math - I am trying to solve a problem using Newton's equation, which is (-1/2)(...